Fatores abióticos, tais como luz e anoxia, durante o crescimento melhoram a virulência e outras qualidades fenotípicas em Metarhizium robertsii - Oliveira, Ariel de Souza (2018)
Light conditions, as well as hypoxia and anoxia during fungal growth, cause several physiological changes in their metabolism, germination, mycelial growth, and conidial production. In this study, conidia of the entomopathogenic fungi Metarhizium robertsii were produced on potato dextrose agar (PDA) medium in the dark; under white light; under blue light; under red light; under continuous hypoxia; transient anoxia, under normoxia; and minimum medium (Czapek medium without sucrose) supplemented with 3 % lactose (MML) in the dark. The conidial production for each treatment as well as the speed of conidial germination, and virulence to the insect Tenebrio molitor were evaluated. The fungus grown under blue light produced more conidia than the fungus grown in the dark. The conidial production of the fungus grown under white and red light were similar to that obtained in the dark, and MML afforded the least conidial production. Conidia produced on MML or on PDA medium under white or blue light germinated faster than conidia produced on PDA medium in the dark or under red light. Conidia produced on PDA medium under white light were more virulent than conidia produced in the dark, under blue light or red light. The fungus grown under hypoxia or transient anoxia produced similar amounts of conidia and germinated at the same speed than the fungus grown under normoxia,. Conidia produced under transient anoxia were more virulent than conidia produced under normoxia and hypoxia, however, were less virulent than conidia produced on MML.